SYNTHESIS AND CHARACTERIZATION OF BIPHASIC CALCIUM PHOSPHATE AND 45S5 BIOACTIVE GLASS COMPOSITE - Fakhrurazi, Umar
Biphasic calcium phosphate (BCP) biomaterial, consisting of hydroxyapatite (HA, Ca5(PO4)3OH) and ?-tricalcium phosphate (?-TCP, Ca3(PO4)2), and bioactive glass (BG) have been extensively studied for their applications in the biomedical field as bone graft materials, implants, and dental fillings. The addition of BG to BCP can enhance the physical properties of the material, such as strength and hardness, increase bioactivity, and introduce antibacterial properties. The bioactivity of bone graft materials is indicated by their ability to form apatite, the main component of bones and teeth. The bioactivity of a material can be determined through in vitro testing in simulation body fluid (SBF). The aim of this study is to synthesize and characterize BCP and BCPG (a mixture of BCP and BG), and to conduct in vitro tests in simulation body fluid. In this experiment, BCP was synthesized from a mixture of HA and ?-TCP, with a mass ratio of HA/?-TCP 60/40, through a mechanochemical process using an agate mortar and pestle. HA and ?-TCP were each synthesized through a co-precipitation reaction at 40 °C. HA was obtained from the reaction between Ca(NO3)2 solution and (NH4)2HPO4 solution, with a molar ratio of Ca/P of 1,67 and a mixture pH of 11. Subsequently, ?-TCP was obtained from the reaction between Ca(NO3)2 solution and (NH4)2HPO4 solution, with a molar ratio of Ca/P of 1,50 and a mixture pH of 9. BCPG was obtained from the mixture of BCP and BG-45S5, with amounts of 2,5% and 5% (w/w). The resulting products were labeled BCPG2.5 and BCPG5. The BG-45S5 used was synthesized via the sol-gel method, containing 45% SiO2; 24,5% CaO; 24,5% Na2O; and 6% P2O5. Powder X-ray diffraction (PXRD) diffractogram results showed changes in the phase ratios of HA and ?-TCP in the BCP due to the addition of BG-45S5. The addition of BG-45S5 to BCP caused a shift in the 2? value to 31,01, indicating the doping of Na+ ions into the ? TCP phase. The morphology of BCP consisted of non-homogeneous, randomly agglomerated particles with an average size of 348 ± 129 nm and micropores of 243 ± 91 nm. With the addition of BG-45S5, the particles de-agglomerated, resulting in smaller, denser particles and reduced micropores. The particle and micropore sizes for BCPG2.5 were 305 ± 172 and 175 ± 54 nm, respectively, while for BCPG5 they were 254 ± 157 and 162 ± 65 nm. Energy dispersive X-ray (EDX) results indicated that the addition of BG-45S5 led to an increase in Na+ and Si4+ ions in BCP. In vitro tests in simulation body fluid (SBF) showed morphological changes with the formation of a new layer on all three samples. These results suggest the formation of apatite on the BCP and BCPG samples, which is the first stage in the bone regeneration process